Psychosocial factors implicated in the development of antisocial personality disorder - Corson, Eliza-Jane (2017)
Evidence suggests that Antisocial Personality Disorder (ASPD) is highly prevalent amongst young males involved in the criminal justice system; however effective psychological treatment options for people with the disorder is limited. This thesis therefore explores psychosocial factors implicated in the development of the disorder, with the view to identify specific treatment targets for psychotherapeutic interventions. In the first instance, a systematic review and meta-analysis was conducted to examine the efficacy of Mentalization Based Therapy (MBT), a psycho-dynamically informed intervention. MBT was originally developed to treat people with Borderline Personality Disorder (BPD), yet to date no meta-analysis has evaluated the efficacy of MBT alone. Furthermore, emerging evidence suggests that MBT can be effective for people with ASPD, however at present, there are insufficient studies to examine the effectiveness of the approach with this population. Therefore, MBT was examined with the view to assess treatment outcomes for adolescents with emerging BPD and adults diagnosed with BPD. In accordance with the specific inclusion criteria, five primary articles were retained and analysed. In relation to the MBT group, there was a significant improvement in symptoms. Furthermore, effect sizes for other problems (anxiety, depression, suicidal attempts/self-harm) were found to be large to very large. When considering interpersonal functioning, interestingly, analysis revealed no effect favouring either the treatment or control group. Regarding impairment, a large and significant effect size was found in favour of the control group. Overall, adolescents derived greater benefit from the treatment when compared to adults. Limitations relate to the number of available studies in this review. In order to identify treatment targets for psychotherapeutic interventions, an empirical study explored the relationship between mentalizing capability, attachment style and schema as predictors of ASPD in 79 men recruited from a Young Offenders Institution (YOI). The results confirmed that anxious attachment style and specific Early Maladaptive Schema (EMS) domains relating to Disconnection & Rejection (mistrust-abuse); Impaired Autonomy & Performance (dependence), and Impaired Limits (entitlement) are associated with ASPD in young male offenders. Inferential analyses confirmed that intellectual functioning did not influence performance on any measures. Main limitations relate to the cross-sectional nature of the study and sample size. Following this theme, a single case study relating to the assessment and treatment of a young male with ASPD and comorbid diagnoses was undertaken using a firesetting offence focused treatment programme. Formulation, treatment progress and outcomes are discussed; and recommendations for further work are provided. Thereafter, a critical appraisal of the Revised Adult Attachment Scale (RAAS; Collins, 1996), a measure utilised in the empirical study was conducted. Consideration is given to the utility of the RAAS, particularly within forensic populations. The RAAS was found to be a reliable and valid measure for use with undergraduate, general, and clinical populations. Further research relating to the application within forensic populations is needed to test the reliability and validity of the tool with offenders. Finally, the thesis discusses limitations of the methodologies used and highlights how the overall aim of this thesis was achieved.